Cross-border credit derivatives linkages - Benedetta Bianch (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper is a first attempt to include credit derivatives in international macrofinancial analysis. We document that gross credit derivatives holdings map to bilateral portfolio investment linkages. On a net basis, our results suggest an asymmetry between sectors and between net buyers and net sellers of CDSs. When a banking system is a net buyer of protection, the protection purchased is proportional to the debt securities held. Conversely, when a banking system is a net seller, the protection sold is proportional to the securities held. For investment funds, we find no aggregate relation between net CDSs and the debt securities held.
Keywords: F34; F21; 330; Cross-border positions; Risk transfer; CDS; EMIR data